Temporal trend of tuberculosis in Brazil - Márcio Cristiano de Melo; Henrique Barros; Maria Rita Donalisio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
The objective was to analyze the temporal trend of tuberculosis incidence rates in Brazilian states and regions to identify patterns and inequalities. We carried out an ecological study of incidence rates per 100,000 inhabitants aged between 20 and 59 years with tuberculosis in Brazil and in their respective states from 2001 to 2017 according to annual percentage change and joinpoint regression. A significant decrease of -15.1% in the annual variation (95%CI: -27.2; -1.0) was observed in Roraima between the years 2003-2007. In the Central Region, Goiás registered an annual average variation of -2.5% per year (95%CI: -3.6; -1.3). Five out of nine Northeastern states had decreasing annual variations throughout the studied series. Espírito Santo and Rio de Janeiro were the states of the Southeast that presented decreasing between 2001-2017. In the Southern Region, the state of Paraná was the only one with the same annual variation of -3.7% (95%CI: -4.1; -3.2). In Brazil, the average annual percentage change was -1.8% (95%CI: -2.4; -1.1). The results of this study showed a decline in the incidence of tuberculosis in Brazil. However, regional and intra-regional differences were observed. Determining the trend pattern of tuberculosis incidence may assist in the planning and implementation of national tuberculosis control policies.